Development of an ADDIE-Based Physics Learning Video to Improve Students' Learning Achievement - Lidyana Febri Engelia; Rendy Wikrama Wardana; Riyanto (KASTA : Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2025)
The integration of instructional technology in physics education has become increasingly important to enhance students' understanding of abstract concepts and improve learning outcomes. However, conventional teaching methods often fail to engage students effectively, resulting in low academic achievement. This study aimed to develop an ADDIE-based physics learning video and evaluate its feasibility, practicality, and effectiveness in improving students' learning achievement. The research employed a Research and Development (R&D) approach using the ADDIE model, which consists of Analysis, Design, Development, Implementation, and Evaluation stages. The learning video was validated by subject matter experts, media experts, and practitioners before being implemented in the classroom. Data were collected through validation sheets, student response questionnaires, and pre-test and post-test assessments. The results indicated that the developed learning video met the criteria of validity and practicality based on expert evaluations and positive student responses. Furthermore, the implementation of the learning video significantly improved students' learning achievement, as demonstrated by the increase in post-test scores compared to pre-test scores. The findings suggest that ADDIE-based physics learning videos can serve as effective instructional media to facilitate students' understanding of physics concepts and enhance their academic performance. Therefore, the integration of well-designed learning videos into physics instruction is recommended to support more engaging and effective learning experiences.